Psychiatry and narcology. Schizophrenia, schizotypal, delusional and affective disorders, clinic and treatment : tutorial for 4th year students - Safonov, D. M.; Сафонов, Дмитро Миколайович (Запорізький державний медичний університет, 2022)
The tutorial provides materials on modern ideas about methods of diagnosis and treatment of schizophrenia, schizotypal, delusional and affective disorders and covers 21.9% of the curriculum program «Psychiatry and narcology» for the 4th year students of International Faculty №2. The authors used modern requirements for teaching, control of theoretical knowledge, skills and practical abilities in the system of credit transfer of educational evaluation. The materials of tutorial should help students to improve their knowledge and skills in the basic methods of diagnosing of mental pathology, expand their understanding of this kind psychopathology. The tutorial is a guide for conducting practical classes in psychiatry and were developed for the first time. Due to the progressive development of psychiatry, changes in the requirements for specialists, this tutorial will not meet the pedagogical and professional needs over time, so it will be improved and supplemented.